2014
DOI: 10.12809/hkmj134065
|View full text |Cite
|
Sign up to set email alerts
|

Live birth rate, multiple pregnancy rate, and obstetric outcomes of elective single and double embryo transfers: Hong Kong experience

Abstract: Objective: To compare the live birth rate, multiple pregnancy rate, and obstetric outcomes of elective single and double embryo transfers.Design: Case series with internal comparisons.Setting: University affiliated hospital, Hong Kong. Participants:Between October 2009 and December 2011, 206 women underwent their first in-vitro fertilisation cycle. Elective single embryo transfer was offered to women who were aged 35 years or below, and had endometrial thickness of 8 mm or more and at least two embryos of good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…Rate of implantation, cumulative pregnancy rates per transfer, and cumulative live birth delivery were similar among both groups. Similar results were obtained in other settings [ 71 , 72 ]. In a recent Cochrane review [ 73 ], the policy of single embryo transfer versus two embryo transfer was evaluated regarding pregnancy rates.…”
Section: Methodssupporting
confidence: 90%
“…Rate of implantation, cumulative pregnancy rates per transfer, and cumulative live birth delivery were similar among both groups. Similar results were obtained in other settings [ 71 , 72 ]. In a recent Cochrane review [ 73 ], the policy of single embryo transfer versus two embryo transfer was evaluated regarding pregnancy rates.…”
Section: Methodssupporting
confidence: 90%
“…This is a very reassuring result that should be taken into consideration, when performing AR Technologies in this group of patients, to avoid multiple gestations and their undesired consequences. Similar results have already been published for this age group (Koryntová et al, 2005;Yang et al, 2012;Chai et al, 2014). The present study divided patients into four age groups as recent reports have been using this system when describing women´s fertility status (Morin et al, 2014).…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies showed that multiple pregnancy rates were increased with DET [5,6,23,24]. Interestingly, Li et al reported a higher multiple pregnancy rate in DET with two good quality embryos when compared with DET with one good and one poor quality embryo, and related this finding with the higher implantation rate of good quality embryos.…”
Section: Group a (Det Withmentioning
confidence: 94%